Taxonomic study of the genus Promalactis Meyrick (Lepidoptera, Oecophoridae) from Hainan Island, China (II) - Hu, Sha; Wang, Shuxia (Zootaxa, 2016)
Ten species of the genus Promalactis Meyrick, 1908 are treated from Hainan Island, China. Eight species are described as new: P. falciprocessa sp. nov.; P. bilobulata sp. nov.; P. longivalvaris sp. nov.; P. pugnivalvata sp. nov.; P. termelliptica sp. nov.; P. gladiata sp. nov.; P. lucida sp. nov. and P. latitaeniata sp. nov.; the male of P. caperatiella Kim et Park, 2014 and the female of P. clavata Du, Li et Wang, 2011 are reported for the first time in science; and P. caperatiella Kim et Park, 2014 is newly recorded in China. Images of adults and genitalia are provided.